Comparison of photosynthetic carbon fixation of Nannochloropsis oceanica cultivated with carbon suppliers: CO2, NaHCO3 and CH3OH. Issue 41 (October 2020) - Wang, Zhenyi; Cheng, Jun; Li, Ke; Zhu, Yanxia; Liu, Jianzhong; Yang, Weijuan; Xu, Jinhui; Park, Ji-Yeon
Highlights: Biomass and carbon fixation with CO2 + methanol increased by 840.9 % and 78.3 %. CO2 + methanol enhanced photosynthetic pigment synthesis by improving glycolysis. NaHCO3 weaken photosynthetic electron transport with non-destructive structure. Translation factor increased 9-fold with methanol and decreased 50 % with NaHCO3 . Methanol reduced carbonic anhydrase and intracellular CO2 /HCO3 − equilibrium. Abstract: To increase the carbon fixation efficiency of Nannochloropsis oceanica cultivated with industrial flue gas and wastewater, typical CO2 suppliers of methanol, NaHCO3 and CO2 were combined with 15 % CO2 flue gas, then compared for their effects on N. oceanica intracellular metabolic and biological regulation. In the presence of CO2 gas with and without its ionized acid (HCO3 − ), microalgal growth was inhibited due to carbon transport-dependent ion transfer and balance. In a weakly acidic environment, growth inhibition was due to cell apoptosis, while in a weakly alkaline environment this was led to cell division inhibition by a decrease of translation initiation factors and carbon fixation stagnation by mass closure of photosynthetic reaction centers. When methanol was combined with 15 % CO2 gas, less negative effects on N. oceanica growth due to changes in the CO2 /HCO3 - equilibrium. The presence of methanol increased light-dependent reactions by providing sufficient substrates for photosynthetic pigment synthesis through enhanced glycolysis. Total carbon fixation was further increased by higher rates of cell division. The biomass yield and carbon fixation efficiency of N. oceanica grown with methanol and 15 % CO2 was 8.4-fold, and 78.3 % greater, respectively, than that of N. oceanica grown with only 15 % CO2 gas.